ALTERNATIF PENGEMBANGAN AKSARA LONTARA ( Alternative Way of Developing Aksara Lontara ) - Abd. Aziz Ahmad (SAWERIGADING, 2009)
AbstractIt has been recognized that the development of “Aksara Lontara” isunsatisfactory, especially in facilitating the punctuation needed to spell the soundof aksara Lontara. Expressing culture through an understanding of locallanguage orthography may give contribution to the connection history of ournation in the past and the present time.The aksara Lontara is used for severalfunctions, such as writing religion book, names of street/road, name plates, andmany others. However, people find difficulties in reading such a spelling ofaksara Lontara. Therefore, punctuation as a sign of consonants for aksaraLontara is required to be developed.In this article, five signs of consonants foraksara Lontara are proposed. They are “o”, “x”, and “Ö” above the letter, “_”below the letter, and the letter written in smaller font, as in m into “m” whichsounds “m”.